Expression of human beta-defensins-1, 2 and 4 mRNA in human lung tumor tissue: a pilot study - Shestakova, T.; Zhuravel, E.; Bolgova, L.; Alekseenko, O.; Soldatkina, M.; Pogrebnoy, P. (Experimental Oncology, 2008)
To analyze the patterns of human beta-defensin-1, 2, 4 (hBDs) expression in human lung tumors. Materials and Methods: Tissue samples of surgically resected human lung tumors (squamous cell carcinoma (SCC), n = 10; adenocarcinoma (AC), n = 10) paired with conditionally normal tissue samples were analized for expression of hBD-1, 2, 4 mRNA by semiquantitive RT-PCR. Results: In a number of studied lung cancer tissue samples, overexpression of defensin mRNA was registered: hBD-1 mRNA (50% of SCC and 60% AC), hBD-2 mRNA (60% of SCC and 50% of AC) or hBD-4 (40% of SCC and 20% AC). No correlation was detected between the levels of hBD-1, hBD-2 and hBD-4 mRNA and histological type, differentiation grade of the tumor, and the stage of the disease, as well as the content of hBD-2 peptide in blood serum of lung cancer patients. Conclusion: Human beta-defensins-1 and -2 are often up-regulated in human lung tumors. Цель: проанализировать особенности экспрессии мРНК бета-дефенсинов-1, 2, 4 (hBDs) в ткани опухоли легкого человека.
Материалы и методы: с помощью метода полуколичественного RT-PCR-анализа изучали уровень экспрессии мРНК
hBD-1, 2, 4 в образцах ткани хирургически удаленных опухолей легкого человека (плоскоклеточный рак — ПКР, n = 10;
аденокарцинома — AК, n = 10) по сравнению с образцами условно-нормальной ткани легкого тех же пациентов. Результаты:
в ряде исследованных образцов опухолей легкого выявлена повышенная экспрессия мРНК hBD-1 (50% ПКР и 60% AК),
hBD-2 (60% ПКР и 50% АК) или hBD-4 (40% ПКР и 20% AК). Зависимости между уровнем экспрессии бета-дефенсинов
и гистологическим типом опухоли, стадией заболевания и содержанием пептида hBD-2 в сыворотке крови больных не
установлено. Выводы: в ткани опухоли легкого человека часто активирована экспрессия hBD-1 и hBD-2.